2019
DOI: 10.1016/j.athoracsur.2019.03.098
|View full text |Cite
|
Sign up to set email alerts
|

National Practice Patterns and Early Outcomes of Aortic Valve Replacement in Children and Teens

Abstract: Background. Several options exist for aortic valve replacement (AVR) in children and teens, but contemporary practice patterns and outcome data are lacking. We describe national AVR practice patterns and early outcomes.Methods. Children (aged 1 to 18 years) in The Society of Thoracic Surgeons Congenital Heart Surgery Database undergoing AVR from 2000 to 2016 were included. Preoperative characteristics, operative data, and outcomes were described. To evaluate practice patterns, centers were assigned tertiles by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Nelson et al recently reported early mortality comparable to the current review in 3446 children undergoing AVR. 36 …”
Section: Discussionmentioning
confidence: 99%
“…Nelson et al recently reported early mortality comparable to the current review in 3446 children undergoing AVR. 36 …”
Section: Discussionmentioning
confidence: 99%
“…In the recent database study of 3446 children who underwent aortic valve replacement, Nelson and colleagues 23 demonstrated that children who underwent aortic valve replacement with a homograft had the highest early mortality. No late mortality or reoperation rate was reported in this large database study.…”
Section: Comparative Studiesmentioning
confidence: 99%
“…[45][46][47] Surgical Valve Replacement in the CHD Patient Mechanical valves are preferred for mitral and AoV replacement in patients younger than 50 years, because they have improved longevity and better hemodynamics in smaller valve sizes. [48][49][50][51][52][53][54] Conversely, mechanical valves do not perform as well in the right heart due to an increased incidence of thrombotic complications. 41 Most pediatric surgeons recommend bioprosthetic valves in the tricuspid and pulmonary positions and mechanical valves in the mitral position and either a mechanical valve or, less commonly, an autograft valve in the aortic position (Ross procedure).…”
Section: Tricuspid Valve Diseasementioning
confidence: 99%